A Pareto-Improving Minimum Wage - Eliav Danziger; Leif Danziger (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper shows that a graduated minimum wage, in contrast to a constant minimum wage, can provide a strict Pareto improvement over what can be achieved with an optimal income tax. The reason is that a graduated minimum wage requires high-productivity workers to work more to earn the same income as low-productivity workers, which makes it more difficult for the former to mimic the latter. In effect, a graduated minimum wage allows the low-productivity workers to benefit from second-degree price discrimination which increases their income.
Keywords: J30; 330; graduated minimum wage; Pareto improvement